PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) TERHADAP PRICE TO BOOK VALUE (NPM) PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rudiyanto Rudiyanto; Puput Putriani (Universitas La Tansa Mashiro, 2017)
This study aims to determine the effect of Return on Equity (ROE) and Debt to Equity Ratio (DER) significantly both simultaneously and partially. The population in this study were 10 Pharmaceutical companies as of August 12, 2016 which were listed on the Indonesia Stock Exchange (IDX) for the period 2011-2016. The sampling technique with purposive sampling technique then only 5 companies were sampled. Quantitative descriptive research method, multiple linear regression data analysis techniques that use SPSS version 20, prerequisite data analysis test with classic assumption test, namely normality test, multicollinearity test, autocoleration test and heteroskadisity test.Partial research results Return on Equity (ROE) has a significant effect on Price to Book Value (PBV) and Debt to Equity Ratio (DER) has no significant effect on Price to Book Value (PBV). Whereas, simultaneously Return on Equity (ROE) and Debt to Equity Ratio (DER) have a significant effect on Price to Book Value (PBV) and the Adjusted R2 test of 45.7% Price to Book Value (PBV) is influenced by Return on Equity ( ROE) and Debt to Equity Ratio (DER) and the remaining 54.3% Price to Book Value (PBV) is influenced by other factors not examined in this study